2021
DOI: 10.1158/1940-6207.capr-21-0073
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Genetic Testing Among Patients with Cancer At Risk for Lynch Syndrome in the National Health Interview Survey

Abstract: Lynch syndrome is the most common inherited cancer syndrome that increases the risk of developing colorectal and endometrial cancer. Universal screening guidelines were first recommended by the Centers for Disease Control and Prevention (CDC) in 2009 and are updated annually by multiple societies. Therefore, one would expect genetic testing rates to increase over time. But testing remains underutilized among those with colorectal or endometrial cancer, even though early detection can improve prognosis and surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Additional factors such as age or prior presentation of T1pos related disease (such as breast cancer for an individual with HBOC) play a role as well. For these and other reasons, it has been shown that the uptake of pre-symptomatic genetic testing is considerably lower than 100% even for at-risk individuals ( Finlay et al, 2008 ; George et al, 2015 ; Menko et al, 2019 ; Actkins et al, 2021 ; David et al, 2021 ). Considering that 9.1% of surveyed T1pos participants with an EHR record had prior, EHR-documented knowledge of their condition and additional participants already had interventions due to prior presentation of their underlying risk, it is perhaps not surprising that just 71% of T1pos Participants with EHR record indicated that they shared their results with their healthcare providers ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors such as age or prior presentation of T1pos related disease (such as breast cancer for an individual with HBOC) play a role as well. For these and other reasons, it has been shown that the uptake of pre-symptomatic genetic testing is considerably lower than 100% even for at-risk individuals ( Finlay et al, 2008 ; George et al, 2015 ; Menko et al, 2019 ; Actkins et al, 2021 ; David et al, 2021 ). Considering that 9.1% of surveyed T1pos participants with an EHR record had prior, EHR-documented knowledge of their condition and additional participants already had interventions due to prior presentation of their underlying risk, it is perhaps not surprising that just 71% of T1pos Participants with EHR record indicated that they shared their results with their healthcare providers ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, screening the general population can only be effective if genetic findings are successfully disseminated to project participants and if a significant portion of the screened individuals follow recommended actions. However, this may not necessarily be the case as it has been shown that the uptake of genetic testing and their results may be sub-optimal and that primary care providers are still not comfortable with genetic testing ( Press et al, 2000 ; Binetti et al, 2006 ; Finlay et al, 2008 ; George et al, 2015 ; Godino et al, 2016 ; Bijlsma et al, 2018 ; Menko et al, 2019 ; Actkins et al, 2021 ; David et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this national analysis of adult self-reported survey data, we found that only a small proportion of individuals undergo genetic testing and/or counseling for CRC risk, even among subgroups of individuals at risk due to family or personal history (3.7%) and those at risk due to personal history of CRC (8.4%). Similarly, Actkins et al also found very low uptake of genetic testing in adults who had CRC and/or endometrial cancer using NHIS survey data [ 22 ]. While genetic testing/counseling is available for inherited cancer syndromes [ 23 ], such as Lynch syndrome or familial adenomatous polyposis, most CRC is not caused by inherited mutations; this may explain our finding of a low rate of genetic testing/counseling for CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other studies using the NHIS to study the utilization of genetic testing and/or counseling [ 22 , 38 , 39 , 40 ]. Actkins et al examined the uptake of genetic testing across 2005, 2010, and 2015 in adults who had CRC and/or endometrial cancer [ 22 ], and found that uninsured individuals had higher rates of genetic testing [ 22 ]. This finding is counterintuitive and conflicts with ours.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Patients at risk for Lynch Syndrome diagnosed with either colorectal or endometrial cancer have even lower levels of testing with one study reporting a rate around 6% and another study reporting a rate around 3%. 6 , 7 Germline genetic testing for patients with cancer can have significant impact on their cancer treatment and surveillance as well as implications for family members.…”
Section: Introductionmentioning
confidence: 99%